1991
DOI: 10.1182/blood.v78.9.2182.bloodjournal7892182
|View full text |Cite
|
Sign up to set email alerts
|

High-dose recombinant interleukin-2 and acute myeloid leukemias in relapse

Abstract: Interleukin-2 (IL-2) is able to induce the regression of metastatic cancers when administered in vivo. IL-2-activated natural killer cells and lymphocytes show, in vitro, activities against leukemic cells. To assess if in vitro observations could have significant clinical relevance, we evaluated the in vivo activity of high-dose recombinant IL-2 (6 to 8 x 10(6) IU/m2/8H intravenous bolus for 5 days) in 10 patients with acute myeloid leukemias (AML) in relapse after chemotherapy (n = 7) or autologous bone marro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Interleukin-2 was the forerunner in this aspect with several studies looking into its potential utility as a maintenance agent. Biologically, interleukin-2 is a potent activator of cytotoxic T cells and natural killer cells; [27][28][29][30][31][32][33] however, multiple well-designed clinical trials from the late 1990s to 2010 failed to show a benefit in leukemiafree survival (LFS) or OS with interleukin-2 as maintenance therapy in children, adults or older patients with AML. [34][35][36][37][38][39] The last in this series was the relatively recently published report of the ELAM02 randomized controlled trial in childhood AML in which patients in remission and not undergoing HSCT after intensive I-C therapy were randomized to receive interleukin-2 or remain under observation; there was no improvement in DFS or OS with the use of interleukin-2.…”
Section: Immune Adjuvantsmentioning
confidence: 99%
“…Interleukin-2 was the forerunner in this aspect with several studies looking into its potential utility as a maintenance agent. Biologically, interleukin-2 is a potent activator of cytotoxic T cells and natural killer cells; [27][28][29][30][31][32][33] however, multiple well-designed clinical trials from the late 1990s to 2010 failed to show a benefit in leukemiafree survival (LFS) or OS with interleukin-2 as maintenance therapy in children, adults or older patients with AML. [34][35][36][37][38][39] The last in this series was the relatively recently published report of the ELAM02 randomized controlled trial in childhood AML in which patients in remission and not undergoing HSCT after intensive I-C therapy were randomized to receive interleukin-2 or remain under observation; there was no improvement in DFS or OS with the use of interleukin-2.…”
Section: Immune Adjuvantsmentioning
confidence: 99%
“…Adult patients with acute leukemia with high levels of cytokine production and NK activity have a lower risk of relapse 16 . Preliminary nonrandomized clinical trials on patients with recurrent AML showed a potential effect of IL2, with remission and long‐term survival observed in some cases 17,18 . The potential antileukemic effects of IL2 13,14,19 and its limited toxicity at high doses 17,18,20 suggested that the prolonged administration of lower doses might be a useful consolidation treatment to prevent relapse in patients not undergoing HSCT 20,21 …”
Section: Introductionmentioning
confidence: 99%
“…16 Preliminary nonrandomized clinical trials on patients with recurrent AML showed a potential effect of IL2, with remission and long-term survival observed in some cases. 17,18 The potential antileukemic effects of IL2 13,14,19 and its limited toxicity at high doses 17,18,20 suggested that the prolonged administration of lower doses might be a useful consolidation treatment to prevent relapse in patients not undergoing HSCT. 20,21 ELAM02 was a prospective, national, multicenter, randomized controlled trial (RCT) assessing the benefits of 1 year of IL2 maintenance therapy in patients with primary pediatric AML.…”
Section: Introductionmentioning
confidence: 99%